2017
DOI: 10.1080/08916152.2017.1283373
|View full text |Cite
|
Sign up to set email alerts
|

Transient heat transfer for helium gas flowing over a horizontal cylinder in a narrow channel

Abstract: Transient forced convection heat transfer due to exponentially increasing heat input to a heater is important as a database for the safety assessment of the transient heat transfer process in a very high temperature gas-cooled reactor (VHTR). Forced convection transient heat transfer for helium gas flowing over a cylinder in a narrow channel was experimentally studied at various periods of exponential increases in heat input. The test heater was mounted *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to our early research, it is observed that the transition point of period τ for heat transfer coefficient does not show much dependence on velocity because we have rose up the flow velocity to 150 m/s in a narrow channel (Liu et al, 2017). Besides, the effects of gas pressure, initial gas temperature, initial heat generation rate, and structure of the heating surface on transition point are not obvious according to this research and our wide range experiments (Liu et al, 2008;Liu et al, 2014;Liu et al, 2017). Early research by Chao and Cheema (1967) indicated that the response time of the thermal layer due to a step change in wall flux varies directly as Pr 1/3 with Pr ranged from 0.72 to 100.…”
Section: Response Analysis For Heat Transfer Interface Of Solid and Fluid Areamentioning
confidence: 90%
See 1 more Smart Citation
“…According to our early research, it is observed that the transition point of period τ for heat transfer coefficient does not show much dependence on velocity because we have rose up the flow velocity to 150 m/s in a narrow channel (Liu et al, 2017). Besides, the effects of gas pressure, initial gas temperature, initial heat generation rate, and structure of the heating surface on transition point are not obvious according to this research and our wide range experiments (Liu et al, 2008;Liu et al, 2014;Liu et al, 2017). Early research by Chao and Cheema (1967) indicated that the response time of the thermal layer due to a step change in wall flux varies directly as Pr 1/3 with Pr ranged from 0.72 to 100.…”
Section: Response Analysis For Heat Transfer Interface Of Solid and Fluid Areamentioning
confidence: 90%
“…Exponentially increasing heat generation rate was added to the tube, and the transient heat transfer coefficient of the tube was analyzed. In our previous research, Liu et al (2008), Liu et al (2014), andLiu et al (2017) experimentally studied the transient heat transfer process for parallel flow of helium gas over a horizontal cylinder and a flat plate. An exponential increasing heat generation rate was applied for the transient heating condition.…”
Section: Introductionmentioning
confidence: 99%
“…A hot gas duct Figure 5.2 illustrates the second sample problem. This problem is based on a hot gas duct design in a helium engineering demonstration loop (HENDEL) with an intended use for high temperature gas-cooled reactors [41]. The loading condition and material considered here are different from the original design.…”
Section: Sample Problem-2mentioning
confidence: 99%
“…They developed an empirical correlation, which presented the experimental data within ±20%. Liu et al (2014Liu et al ( , 2015Liu et al ( , 2017 experimentally studied transient heat transfer for helium gas flowing over test heater with various shapes which are horizontal plates, twisted plates and cylinders. Shibahara et al (2017) carried out experiments and measured transient heat transfer coefficients for water flowing in a narrow tube.…”
Section: Introductionmentioning
confidence: 99%